Negotiating Dual Religiosity of African Indigenous Religion and Christianity: Challenges, Tensions and Prospects among Bemba Catholics in Muchinga Province, Zambia - Armstrong Chanda; Austin Mumba Cheyeka; Tomaida L.C Milingo (YASIN, 2026)
Although the coexistence of Catholicism and African Indigenous Religion (AIR) among Bemba Catholics in Muchinga Province, Zambia, remains underexplored, it often produces religious friction, identity tensions, and frustration in lived religious experience. This study examined the challenges, tensions, and prospects involved in negotiating the dual religiosity of Bemba Catholics who practice Catholicism alongside AIR. Using a qualitative design grounded in hermeneutic phenomenology, the study involved 20 Bemba Catholic participants and drew data from in-depth interviews, focus group discussions, and observations. The data were analyzed using Van Manen’s thematic reflection approach. The findings reveal that negotiating dual religiosity presents multiple challenges, including conflicting beliefs, social stigma, excommunication and disciplinary pressures, and tensions between Christian faith and ethno-religious identity. The study also identified inadequate integration of faith and culture, misconceptions and misinterpretations of Bemba traditional beliefs and practices, and resistance to change within the church as key sources of tension. At the same time, the findings indicate prospects for constructive dialogue with the church and personal development among adherents. This study contributes a contextualized understanding of dual religiosity by foregrounding local cultural complexities in the interpretation of religious identity and practice. It concludes that open discussion is necessary to address the tensions surrounding dual religiosity and recommends that the church develop programs to educate both clergy and laity on the cultural relevance of indigenous beliefs and practices.